Penerapan Metode Belajar Kelompok dengan Tutor Sebaya untuk Meningkatkan Hasil Belajar PKn Siswa Kelas XI IPA 2 SMA Negeri 1 Gedeg Kabupaten Mojokerto - Khurrotin A'yuni (SCHOLASTICA: Jurnal Pendidikan dan Kebudayaan, 2019)
Group Learning method with peer tutor is one of learning methods which involves students in group to learn togethernto solve one problem in one learning material. However, how to ensure that the method will make the students have active roles, motivations, interest, and learning results better? Thus, the problems of the research are (i) Is the implementation of group learning method with peer tutor can improve civic education learning results of class XI IPA 2 students at SMA Negeri 1 in Gedeg? (ii) fow are the students activities during the learning? (iii) How are the students learning interest after the implementation of learning method with peer tutor? The objectives of the research are to discover and analyze (i) whether the implementation of group learning method with peer tutor can improve civic education learning results of class XI IPA 2 students at SMA Negeri 1 in Gedeg; (ii) the students activities during the learning (iii) the students learning interest after the implementation of learning method with peer tutor. The research employed quantitative and qualitative. Data was collected through learning result test, questionnaire, analysis, and observation. The results of the research reveal that (i) the implementation of group learning method with peer tutor can improve civic education learning results of class XI IPA 2 students at SMA Negeri 1 in Gedeg, (ii) the students activities are more improve, (iii) the students learning interests are more improve as well.